Cardiac valve disease: an unreported feature in Ehlers Danlos syndrome arthrocalasia type? - Melis Daniela; Cappuccio Gerarda; Ginocchio Virginia; Minopoli Giorgia; Valli Maurizia; Corradi Massimiliano; Andria Generoso (BMC, 2012)
Abstract Ehlers Danlos syndrome (EDS) athrocalasia type (type VII), is characterized by joint hypermobility, skin hyperextensibility and tissue fragility. No heart involvement has been reported. Two forms have been described: type VII A and VII B. The abnormally processed collagen α2(I) and the skipping of the exon 6 in COL1A2 gene are typically detected in EDS type VII B. We describe a seven-year old female, with a phenotype consistent with EDS type VII B and a diagnosis further confirmed by biochemical and molecular analyses. Cardiac ultrasound showed normal data in the first year of life. When she was 5 years old, the patient developed mitral valve regurgitation, and aortic and tricuspidal insufficiency at 7 years of age. To our knowledge, this is the first report of cardiac valvular involvement in EDS VII B. This feature probably has been underreported for the limited follow-up of the patients. Echocardiography might be warranted in the clinical assessment of EDS VII patients.